2020
DOI: 10.1002/cctc.202000150
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Hydrogenation of Nitroarenes to Anilines with Highly Active in‐situ Generated Copper Nanoparticles

Abstract: Metal nanoparticles (NPs) are usually stabilized by a capping agent, a surfactant, or a support material, to maintain their integrity. However, these strategies can impact their intrinsic catalytic activity. Here, we demonstrate that the in‐situ formation of copper NPs (Cu0NPs) upon the reduction of the earth‐abundant Jacquesdietrichite mineral with ammonia borane (NH3BH3, AB) can provide an alternative solution for stability issues. During the formation of Cu0NPs, hydrogen gas is released from AB, and utilize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…18a and b). 302 The synthetic mineral consisted of cuboid-shaped single crystals, indicating the formation of Cu 0 NPs before and after the reaction, while the size of the Cu 0 NPs was in the range of 20–40 nm after the reaction was complete. 302 The in situ -prepared Cu 0 NPs demonstrated catalytic activity for the hydrogenation of nitrobenzene to aniline in a mixture of MeOH and H 2 O at 25 °C (Fig.…”
Section: Applications Of Cu and Cu-based Nmsmentioning
confidence: 99%
“…18a and b). 302 The synthetic mineral consisted of cuboid-shaped single crystals, indicating the formation of Cu 0 NPs before and after the reaction, while the size of the Cu 0 NPs was in the range of 20–40 nm after the reaction was complete. 302 The in situ -prepared Cu 0 NPs demonstrated catalytic activity for the hydrogenation of nitrobenzene to aniline in a mixture of MeOH and H 2 O at 25 °C (Fig.…”
Section: Applications Of Cu and Cu-based Nmsmentioning
confidence: 99%
“…Interestingly, AB is selectively decomposed by SION-X to H 2 , without borane formation. 53,54 Unlike other copper sources, this mineral can be reformed quantitatively after the transfer hydrogenation reaction by exposure of the solution to the air. The mechanism behind the self-healing properties of these CuNPs is discussed in refs 53 and 54.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the CFSs loading DOX and PXT had a better ability to kill cancer cells. The synergistic effect of DOX and PXT exhibited excellent antitumor efficiency toward various solid tumors, such as breast cancer, by blocking off cells in the G2 m phase [ 26 , 27 ]. Furthermore, polydopamine or methacrylic acid copolymer-modified polycaprolactone (MAC−PCL) could also be introduced into this system to achieve NIR-triggered or pH-responsive drug release.…”
Section: Introductionmentioning
confidence: 99%